HOW EMOJIS AND CODE-SWITCHING SHAPE ONLINE ENGLISH COMMUNICATION - Zafarova Nilufar Zafar qizi; Isaqulova Bakhtigul Khojamovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In the era of digital communication ,written language has evolved into new forms that reflect the dynamic interaction between technology and human expression. English,as a global lingua franca is widely used by non-native speakers who often blend their mother tongue with English in online communication.In such contexts,emojis and code-switching(the alternation between two or more languages within a conversation) play crucial roles in shaping meaning ,tone and social identity.Emojis provide emotional cues and pragmatic nuances that are absent in text based communication,while code-switching expresses cultural belonging ,group membership and personal identity.This article explores how emojis and code-switching function in online English communication ,using qualitative analysis of real-life chat examples from social media and messaging apps.The findings suggest that emojis and code-switching enrich online communication by making it more expessive ,socially contextualized and emotionally accurate.